The Evolution of Qur'anic Interpretation In the First Three Centuries of Islam - Yusuf Olawale Owa-Onire Uthman (IJISH (International Journal of Islamic Studies and Humanities), 2021)
This study deals with the historical development of the exegesis of the Noble Qur'an from the first century of Islam to the end of the third century. It explains the events that elevated tafsir in this era. During these periods, the study of tafsir has gradually gained methodical activity; the Prophet's teachings to the noble Companions was the highest development towards the evolution of Quranic exegesis. However, the Prophet taught them the Qur'an and solved their problem concerning the understanding of the Quran. The paper highlights the striving of the companions in devoting their lives to learning the Qur'anic Tafsir. Therefore, the mainstream exegesis is traced to the Prophet PBUH and his companions. Then the research also elucidates the exegetical position of the successors after the companions to extend the era of the genesis of tafsir to the third century. Lastly, the study listed the scholarly roles played by these golden generations of Islam to achieve the knowledge of the authentic meaning of the Qur'an and its connotations. However, current scholars are highly advised to employ academic efforts on the study of Qur’anic exegesis in line with the direction of these three Muslim’s generations.